Sierra Leone : Staff Report for the 2004 Article IV Consultation, the Fifth Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria and Extension of Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Sierra Leone's 2004 Article IV Consultation, the Fifth Review Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Waiver of Performance Criteria. Growth prospects in the medium term are encouraging, largely based on some mining projects coming to fruition, agricultural expansion, and service-related activities. Real growth is projected in the range of between 6 percent and 7 percent in 2005-07, reflecting these activities in the country's post-conflict phase. Inflation is expected to revert to low single digits, while the current account deficits would narrow, aided by growth in mineral exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet